(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The development of digital technology and social media has changed consumer behavior in seeking information before making purchasing decisions, including in choosing a place to eat. This study aims to analyze the influence of Electronic Word of Mouth (E-WOMa) on brand image, perceived value, and purchase intention in casual dining restaurants in Surabaya. This study uses a quantitative approach with an explanatory research type. Data were collected through online questionnaires distributed to Generation Z in Surabaya who know or have visited casual dining restaurants. The sampling technique used non-probability sampling with a total of 144 respondents. Data analysis was conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS application. The results show that E-WOM has a positive effect on consumer brand image and perceived value. In addition, brand image and perceived value have also been shown to influence consumer purchase intention. These findings indicate that consumer digital communication plays a crucial role in shaping brand perception and purchase intention, so businesses need to optimize digital marketing strategies and manage consumer reviews effectively.